Politik Pendanaan Kampanye dalam Pemilihan Presiden 2019 - Abdul Rahman Ma'mun; Meidi Kosandi (LITERATUS, 2020)
This paper discusses the politics of campaign funding in the Presidential Election 2019 with a focus on the dimension of receiving large campaign fund contributions from oligarchs to the Presidential Candidates and Vice Presidential Candidates for Jokowi-Ma'ruf and Prabowo-Sandi and the dimension of repayment to contributors and voters at post-presidential election. In this regard, this paper also discusses the pattern of funding for the Jokowi-Ma'ruf campaign as the winner of the 2019 Presidential Election, which influenced the changes in the form of the oligarchic political structure resulting from the Presidential Election 2019. The analysis of this paper is based on Jeffrey A. Winters' Oligarchy theory which is supported by the concept of funding campaign from USAID by relying on secondary data on the campaign fund reports of Jokowi-Ma'ruf and Prabowo-Sandi which were reported to the KPU and audited by a public accounting firm. The offered argument is that the politics of campaign funding of the Jokowi-Ma'ruf pair as the winner of the Presidential Election 2019, involving large contributors from the oligarchs, influenced the change in the oligarchic nature of the government, as a result of the Presidential Election, namely the change in the nature of oligarchic involvement in coercion and power from being divided into collective, and the change from being wildly competing among oligarchs to being lenient in cooperation in government.